2014
DOI: 10.1097/bor.0000000000000086
|View full text |Cite
|
Sign up to set email alerts
|

Advances in lupus genetics and epigenetics

Abstract: Purpose of review Genome-wide association studies (GWAS) have identified more than 50 robust loci associated with SLE susceptibility, and follow-up studies help reveal candidate causative genetic variants and their biological relevance contributing to the development of SLE. Epigenetic modulation is emerging as an important mechanism for understanding how the implicated genes interact with environmental factors. We review recent progress towards identifying causative variants of SLE-associated loci and epigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 103 publications
1
68
0
Order By: Relevance
“…How T cells become hyperactive during SLE remains to be determined. However, both genetic background and environmental factors are believed to contribute to the development of SLE [3]. A number of epidemiological studies have suggested that onset and flares of SLE are associated with infection [4].…”
mentioning
confidence: 99%
“…How T cells become hyperactive during SLE remains to be determined. However, both genetic background and environmental factors are believed to contribute to the development of SLE [3]. A number of epidemiological studies have suggested that onset and flares of SLE are associated with infection [4].…”
mentioning
confidence: 99%
“…In particular, the disease is associated with inheritance of MHC class II and class III loci [1][2][3][4]. Two haplotypes of the MHC class II HLA-DRB1 (DRB1*1501 and DRB1*0301) display the strongest association with lupus.…”
Section: Genetics Of Slementioning
confidence: 99%
“…End tissue damage is eventually supported by mechanisms that play an additional role at the local level ( Fig. 1) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…GWASs have identified more than 50 robust loci and genetic variations associated with SLE susceptibility [Han et al, 2009;Yang et al, 2010;Okada et al, 2012;Lee et al, 2014]. Only few of the variants (SNPs) lead to gain or loss of function of the encoded proteins, whereas the majority falls in noncoding regions [Deng and Tsao, 2014]. For example, IRF5, 7, and 8 are transcription factors required for activating transcription of IFN-α and IFN-inducible genes.…”
Section: ) Collect All Genetic and Epigenetic Aberrations For Diagnomentioning
confidence: 99%
“…The research efforts accumulated in the last decades have been able to track the pathogenic origin of SLE to both genetic susceptibility and epigenetic variations arising from environmental factors [Sestak et al, 2007;Morel, 2010;Hedrich and Tsokos, 2011;Hughes and Sawalha, 2011;Deng and Tsao, 2014]. For example, environmental factors such as smoking, nutrition, viral infection, and the exposure to chemicals can trigger immunologic events to eventually result in SLE via epigenetic mechanisms [Costenbader et al, 2012].…”
mentioning
confidence: 99%